Firm Value Determinants: Empirical Evidence from Manufacturing Firms Listed on the Indonesia Stock Exchange - Fadhilah, Nisrina Nur; Kurniati, Destria; Suherman, Suherman (Interdisciplinary Social Studies, 2022)
The company's objectives can be achieved through the implementation of appropriate financial management functions because every financial decision taken will affect other financial management decisions and will have an impact on the value of the company. This study aims to determine the effect of dividend policy, profitability, capital structure, liquidity, and firm size on firm value. The data used in this study was secondary data obtained from manufacturing companies located in the Indonesia Stock Exchange from 2016 to 2019. Data collection method used is purposive sampling method, which resulted in 50 companies during four years of observation. The analysis technique used in this research is data panel regression. The results of the model-1 research show that DPR, ROA, DER, CR, and SIZE, together influence PBV with adjusted R2 of 64,4%. Individually, DPR and ROA have a positive and significant effect to firm value, while CR, DER and SIZE have no significant effect on firm value. The results of the model-2 research show that DPR, ROA, DER, CR, and SIZE, together influence Tobin’s Q with adjusted R2 of 45,8%. Individually, DPR and ROA have positive and significant effect to firm value, while CR, DER, and SIZE have no significant effect on firm value.